Essays on contemporary events (1936-1946) - "Jung, Carl Gustav" (London, 2002)
The book define was the leading psychologist of his time a Nazi sympathiser? This was the question asked by many after the Second World War, as they sought to explain Jung's actions and publications during Nazi rule. So great was the controversy that his reputation risked being permanently damaged. Essays on Contemporary Events was the first broadside in his vigorous defence of his beleaguered reputation. This remarkable work is essential reading for anyone seeking to understand Jung. It will enable the reader to decide: was Jung wholly innocent of the accusations or had he, like so many others, fallen under the Nazi spell and was now trying to make amends.
Keywords: "Contemporary events,1936-1946"